Avaliação dos efeitos cardiovasculares do imatinibe em pacientes comleucemia mielóide crônica - Milena Soriano Marcolino (2008)
Background: Imatinib mesylate (IM), a tyrosine kinase inhibitor that targets BCR-ABL, PDGFRA and c-kit, has become the first line of therapy for patients with chronic myeloid leukemia (CML) and advanced gastrointestinal stromal tumors (GIST). A recent publication suggests that IM might have myocardial toxicity. It reported ten individuals who developed severe congestive heart failure while on imatinib and cardiomyocite abnormalities on electron microscopy. Retrospective studies, however, do not show an increase in heart failure rates inpatients on IM therapy. Nevertheless, these studies have strong methodological limitations, like the retrospective nature, the use of methods which are not considered sufficiently sensitive to recognize heart failure, the insufficient time of follow-up and lack of ventricular function assessment in all patients included. Thereby the cardiotoxicity of imatinib remains a controversial issue. Methods: In order to evaluate IM cardiotoxicity, we recruited 160 patients at the Hematology Service of the Federal University of Minas Gerais, 103 patients with CML on treatment with IM and 57 patients with myeloproliferative disorders as control group. After informed consent, all patients underwent a complete clinical evaluation (interview and physical examination), blood samples for B-type natriuretic peptide (BNP) were taken and a 12-lead electrocardiogram and an echocardiographic study were performed. Results: IM patients were slightly younger (median 48 vs. 54 years, p=0,025), but groups weresimilar regarding gender distribution and cardiac risk factors, except for hypertension (lower prevalence in IM group: 27% vs. 46% in controls, p=0,002). Median time of IM treatment was 844 (range 50-2122) days.Cardiac symptoms and signs were equally distributed between groups, except for peripheral edema, more frequent in IM group (26% vs. 11%, p=0,025). There was no statistical difference regarding BNP levels [median 11 (interquartile range 8-22) vs. 13 (8-27) pg/mL, p=0,213] andejection fraction [median 69 (64-73)% vs. 68 (65-74)%, p=0,67] for IM and control group, respectively. Four patients presented BNP level above the upper normal limit in IM group; one of them presented an ejection fraction below normal (38%). This patient did not have other risk factors for heart disease. In control group, no patients had altered BNP levels or ejection fraction. Conclusions: This study showed that a systematic deterioration of cardiac function mediated by IM therapy was not observed. However, since some patients presented with alteration of BNP and/or ejection fraction, there is still a possibility for isolate cardiotoxicity associated with IM. BNP may be useful as a screening test to identify patients at risk for subsequent CHF while on IM therapy.